Pengaruh Likuiditas, Solvabilitas, Aktivitas, dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Sub Sektor Otomotif Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2019 - 2022 - Hepitasari, Erika; Widuri, Trisnia; Nadhiroh, Umi (Universitas Maritim AMNI Semarang, 2024)
This study aims to determine the Effect of Liquidity, Solvency, Activity, and Profitability on Company Value in Automotive Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2022 Period. This type of research is quantitative research and has a total population of 15 companies. For sample collection, this study uses a purposive sampling technique to obtain a sample size of 10 companies. The data was analyzed using panel data regression through the Eviews 10 program. Based on the results of the partial test, Liquidity (Current Ratio), Solvency (Debt to Equity Ratio), and Activity (Total Assets Turn Over) have a negative and insignificant effect on Company Value (Price to Book Value), while Profitability (Return on Assets) has a positive and significant effect on Company Value (Price to Book Value). Simultaneously, Liquidity (Current Ratio), Solvency (Debt to Equity Ratio), Activity (Total Asset Turnover), and Profitability (Return on Assets) have a significant effect on Company Value.